Application of GC-FID and GC-MS for assessing PAHs in suspended dust - Weglarz, A; Skrok, R (Central European journal of public health, 2000)
The social concern about polycyclic aromatic hydrocarbons (PAHs) is due to the awareness that several of them are carcinogens and are present in polluted air. Several epidemiological investigations have tried to assess the influence of air pollution on the incidence in the population (1). Some authors have suggest that 1-10% of the incidence of lung cancer is caused by air pollution (2, 3). Several sources, e.g. traffic, oil heating, wood stoves, industry may contribute PAHs to the air pollution. Therefore continuous air pollution control applying selective and precise analytical procedures is needed. The submitted work presents results of examination of sixteen polycyclic aromatic hydrocarbons [naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene, anthracene, fluoranthene, pyrene, chrysene, benzo(a)anthracene, benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(a)pyrene, indeno(1,2,3-cd)pyrene, dibenzo(a, h)anthracene, benzo(ghi)perylene] settled on particles of 10 microns fractions of ashes, emitted from industrial and communication sources. Samples of suspended dust were collected at twelve measuring points, from May to June 1998, in 24-hour cycles, in accordance with US EPA methodology. PAHs were extracted from suspended dust in a Soxhlet apparatus and then exposed to extraction in a liquid-solid system (solid extraction-SPE) to eliminate redundant pollution, which may interfere with compounds by determined analysis. Samples were then analyzed using by capillary gas chromatographs "Varian" model 3400 with FID and MS detectors. Results of analysis make it possible to determine the influence of industry and traffic on atmospheric pollution, to compare results of two analytical methods (GC-FID and GC-MS).
Keywords: Chromatography, Gas; chromatografie plynová; Poland; polycyklické sloučeniny; látky znečišťující vzduch; prach; Air Pollutants; Polycyclic Compounds; Polsko; Dust